Improvement of SERS signal measured by portable Raman instrument using random sampling technique - Van Tien, Nguyen; Trong Nghia, Nguyen; Thi Ha Lien, Nghiem; Duong, Vu; Quang Hoa, Do; Chi Dung, Duong; Nguyen Nhue, Phan; Minh Hue , Nguyen (Vietnam Journal of Science and Technology, 2022)
In recent years, portable Raman spectrometers and commercialized surface-enhanced Raman scattering (SERS) substrates have become increasingly popular. They have turned out to be great tools for both substance detection, identification, and analysis on-site. This work addresses the technique to collect proper Raman spectra using SERS substrates and portable Raman spectrometers. We propose a random sampling technique that gives representative and high-quality spectra with high intensity and good resolution. This technique was tested on a home-built portable Raman spectrometer and SERS substrates based on metal film over nano-sphere (MFON) structure. Experimental results showed that peaks of Raman spectrum collected using random sampling technique are significantly narrower than those of spectra measured in conventional one and prevent samples and SERS substrates from photoinduced degradation. Potentially, this method can promote quantitative SERS and chemical trace analysis using portable Raman spectrometers.